Utilization of Blockchain Technology in Increasing Transparency and Effectiveness of Financial Audits - YUDIARTHA, I Made; SASTRAWAN, I Komang Agus Adi; ANDIKAYANA , I Made Dwi; MAULANA, Ilham (Journal Management and Hospitality, 2024)
Financial audits serve as an important tool to ensure that financial statements are prepared accurately and that organizations fulfill their responsibilities to stakeholders. However, traditional audit approaches often face various obstacles, such as delays in accessing information, potential data manipulation, and a lack of transparency in their implementation. Amid these challenges, blockchain technology has emerged as a promising alternative to encourage a more open, efficient, and reliable audit process. Through a literature review, this paper explores the extent to which blockchain technology can be utilized to improve the quality of transparency and efficiency in the implementation of financial audits. Through the Systematic Literature Review method, the results of the study show that the use of blockchain in audits can provide direct (real-time) audit evidence, minimize the risk of data manipulation, and support the implementation of continuous audits. However, there are a number of obstacles that need to be overcome, including infrastructure readiness, personal data protection, and a regulatory framework that is not yet fully supportive. Therefore, this article provides several recommendations aimed at auditors, management, and regulators so that they can optimize the use of blockchain in a more transparent and accountable reporting and audit system.